2015
DOI: 10.1371/journal.pone.0138392
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetics: From Bioinformatics to Rational Design of Dendrimers as Gene Carriers

Abstract: Biomimetics, or the use of principles of Nature for developing new materials, is a paradigm that could help Nanomedicine tremendously. One of the current challenges in Nanomedicine is the rational design of new efficient and safer gene carriers. Poly(amidoamine) (PAMAM) dendrimers are a well-known class of nanoparticles, extensively used as non-viral nucleic acid carriers, due to their positively charged end-groups. Yet, there are still several aspects that can be improved for their successful application in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In this regard, previous studies have suggested that dendrimers can display a propensity to bind some nucleotide bases with better affinity. Maiti and coworkers [ 41 ] have performed theoretical studies with homopolymers—i.e., poly G, poly T, poly A, and poly C—and revealed that the interaction energy between PAMAM-NH 2 and poly G/poly C are the most favorable, in comparison with poly A and poly T. In fact, a recent article of our group [ 42 ] has shown that lysine-terminated dendrimers, bearing amine moieties like native PAMAM-NH 2 , can bind guanine bases in a double-strand DNA with the highest propensity, which was correlated with the information given by protein–DNA interaction obtained from a total of 2013 crystal structures. To determine here if PAMAM-NH 2 shows any propensity to bind better some bases, we calculated the interaction energy over the last 10 ns of MD trajectory, between amine terminal groups and a single base (A, C, G, T) of the asODN (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, previous studies have suggested that dendrimers can display a propensity to bind some nucleotide bases with better affinity. Maiti and coworkers [ 41 ] have performed theoretical studies with homopolymers—i.e., poly G, poly T, poly A, and poly C—and revealed that the interaction energy between PAMAM-NH 2 and poly G/poly C are the most favorable, in comparison with poly A and poly T. In fact, a recent article of our group [ 42 ] has shown that lysine-terminated dendrimers, bearing amine moieties like native PAMAM-NH 2 , can bind guanine bases in a double-strand DNA with the highest propensity, which was correlated with the information given by protein–DNA interaction obtained from a total of 2013 crystal structures. To determine here if PAMAM-NH 2 shows any propensity to bind better some bases, we calculated the interaction energy over the last 10 ns of MD trajectory, between amine terminal groups and a single base (A, C, G, T) of the asODN (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Related to this, a new bioinformatics-based strategy for the rational design of new dendrimers as DNA carriers that employs the knowledge of protein-DNA interactions was recently reported. 3 Among the dendrimers with potential applications, hydroxyl-terminated PAMAM (PAMAM-OH) dendrimers are suggested safe drug carriers due to non-toxic effects observed during in vitro and in vivo applications. 4 Furthermore, the PAMAM-OH dendrimer can preferentially distribute in the brain, enabling targeted therapeutic delivery in disorders such as cerebral palsy, Alzheimer's disease, and multiple sclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Due to a positive charge at physiological pH, PAMAM-NH 2 dendrimers are efficient nucleic carriers 11 12 . Terminal groups theorised to increase the gene carrying abilities of dendrimers include amino acids 13 14 , cell-penetrating peptides such as GALA 11 , and polyethylene glycol groups on dendrimer surfaces 15 , among others.…”
mentioning
confidence: 99%